Two Models to Conduct Nonphysician-led Exercise Stress Testing in Low to Intermediate Risk Patients. Issue 1 (March 2017) - Scott, Adam; Whitman, Mark; McDonald, Alice; Webster, Meghan; Jenkins, Carly
Abstract : Background: Exercise stress testing (EST) is a noninvasive procedure that aids the diagnosis and prognosis of a range of cardiac pathologies. Reduced access is recognized as a limiting factor in enabling early access to treatment or safe and appropriate discharge. Increased accessibility can be achieved by utilizing nonphysician health practitioners to supervise tests. To implement nonphysician-led EST in clinical environments, there is a need for the development and administration of feasible and effective models. Objective: Via inpatient and outpatient referral, this article aims to present 2 standardized models of care for patients requiring EST for diagnostic and prognostic evaluation of numerous pathologies. Method: An inpatient and outpatient model was implemented at the Royal Brisbane and Women's Hospital and Logan Hospital in Queensland, Australia between July 2013 and December 2015. Tests were performed by 2 cardiac scientists employed by each hospital. All tests were immediately reported by a cardiology advanced trainee registrar or consultant cardiologist. Results: A total of 2095 tests were performed via the 2 models. Overall, 73 had a positive result (3.5%), 120 equivocal (5.7%), 129 inconclusive/submaximal (6.2%), and 1773 negative (85.2%). After further testing, 38 of the patients with positive and equivocal results were diagnosed with flow-limiting coronary artery disease. The remaining patients were resolved as negative through further diagnostic testing or lost to follow up. Conclusions: After implementation of the 2 models, patient flow was improved for earlier discharge, reduced waiting times, or timely identification of possible cardiac pathologies, thereby optimizing patient care.